Implementation of a Smart School Learning system with Internet of Things Technology at SMA Negeri II Binjai - Arpan; Yusup, Mohammad; Ahmad, Aidil (Bahasa Indonesia, 2024)
This research explores the transformative impact of Internet of Things (IoT) technology on learning environments, focusing on the development of a Smart School at SMA Negeri II Binjai. The study aims to investigate the integration of IoT technology to enhance educational practices, improve efficiency, and create an innovative and dynamic learning atmosphere. The research employs a mixed-methods approach, combining qualitative and quantitative methodologies. The design includes the development of a comprehensive IoT system tailored for educational settings, considering both hardware and software components. Implementation strategies involve stakeholder engagement, training sessions, and pilot testing to ensure a smooth transition. Evaluation methods encompass performance testing, usability testing, and security testing to guarantee system reliability. The findings are expected to contribute valuable insights into the effectiveness of IoT technology in fostering innovation and improving the overall learning experience in a secondary school setting. The research not only addresses the technical aspects of building a Smart School but also considers the practical implications and challenges associated with the integration of IoT in education.